Regeneration of Shorea robusta. Gaertn in tropical forest of Palpa district, central Nepal - Basyal, Sarita; Lekhak, HD; Devkota, Anjana (Scientific World, 2011)
A study on the regeneration of the Shorea robusta Gaertn in tropical forest of Palpa district was carried out during June-November, 2005. The altitude of study area ranged from 200 m -700 m asl in north facing slope. The study area was natural forest where, Shorea robusta and Terminalia alata, were dominant species .The size class distribution of Shorea robusta resembled the reverse J-shaped curve indicates better regeneration of sal in study area. Sapling and seedling density of Shorea robusta significantly correlated (p=0.01) but was no significant relation with soil parameter. Keywords: Regeneration; Shorea robusta; Size Class distribution Tropical Forest <!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> <!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> DOI: http://dx.doi.org/10.3126/sw.v9i9.5519 SW 2011; 9(9): 53-56 <!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> DOI: http://dx.doi.org/10.3126/sw.v9i9.5518